Effects of Education and Experience on Primary Care Providers' Perspectives of Obesity Treatments during a Pragmatic Trial. Issue 10 (26th September 2018) - Iwamoto, Sean; Saxon, David; Tsai, Adam; Leister, Erin; Speer, Rebecca; Heyn, Hilde; Kealey, Elizabeth; Juarez‐Colunga, Elizabeth; Gudzune, Kimberly; Bleich, Sara; Clark, Jeanne; Bessesen, Daniel
Abstract : Objective: To examine the impact of a 1‐year pragmatic obesity trial on primary care providers' (PCPs) perspectives of treatment. Methods: PCPs from four intervention clinics (PCP‐I) and five control clinics (PCP‐C) completed pre‐ and postintervention surveys on weight‐loss counseling, comfort discussing obesity treatments, and perceived effectiveness of interventions; questions were rated on 0 to 10 Likert scales. Only PCP‐I received patient updates and education about obesity management. Results: Eighty PCPs completed preintervention surveys (pre: 71% female, 71% physicians); 82 PCPs completed postintervention surveys (post: 66% female, 70% physicians). PCPs were most comfortable discussing exercise before and after the trial (pre PCP‐C: 8.22 [1.44], mean [standard deviation (SD)]; post PCP‐C: 8.37 [1.24]; P = 0.8; pre/post PCP‐I: 7.88 [1.51] vs. 7.80 [1.71]; P = 0.3). PCPs were initially least comfortable discussing phentermine/topiramate extended release (ER) but developed significantly more comfort after the trial, to a greater degree among PCP‐I (pre/post PCP‐C: 2.86 [2.66] vs. 3.73 [2.72], P < 0.001; pre/post PCP‐I: 4.00 [2.57] vs. 6.17 [2.27], P < 0.001). After the trial, both PCPs rated exercise significantly less effective for weight loss, with a greater decrease in effectiveness rations among PCP‐I (pre/post PCP‐C: 7.73 [1.94] vs. 6.93 [2.35], P = 0.017; pre/post PCP‐I: 6.27 [2.69] vs. 5.15 [2.31], P = 0.001). Both PCPs rated phentermine (pre/post PCP‐C: 5.03 [2.05] vs. 5.50 [2.12], P = 0.002; pre/post PCP‐I: 5.70 [1.64] vs. 6.83 [1.18], P = 0.001) and phentermine/topiramate ER (pre/post PCP‐C: 3.91 [2.33] vs. 5.47 [2.54], P < 0.001; pre/post PCP‐I: 5.58 [2.21] vs. 7.02 [1.47], P < 0.001) significantly more effective after the trial, though ratings were higher among PCP‐I. Conclusions: PCPs initially overvalued exercise and undervalued weight‐loss medications. PCPs exposed to education and experience gave higher comfort and effectiveness ratings to weight‐loss medications.